London labour and the London poor. With a new introd. by J.D. Rosenberg (Dover Publications, 1968)
With ills, indices, maps, prts and tabs. [The classical study of the culture of poverty and the criminal classes in the 19th century]. 1-3. The London street-folk. XVIII, 494 p., VI, 511 p., X, 442 p